How Talk and Interaction Unfold in a Digitally Enabled Preschool Classroom. Issue 2 (2nd April 2016) - Theobald, Maryanne; Danby, Susan; Davidson, Christina; Houen, Sandy; Scriven, Brooke; Thorpe, Karen
Abstract : The use of mobile digital devices, such as laptops and tablets, has implications for how teachers interact with young students within the institutional context of educational settings. This article examines language and participation in a digitally enabled preschool classroom as students engage with teachers and peers. Ethnomethodology, conversation analysis and membership categorization analysis are used to explicate video-recorded episodes of students (aged between three and five years) interacting while using a laptop and a tablet. Attending to the sequential organization (when, how) and the context relevance (where) of talk and interaction, analysis shows how the intersection of interactions involving the teacher, students and digital devices shapes the ways that talk and interactions unfold. Analysis found that the teacher–student interactions were jointly arranged around a participation framework that included: (1) the teacher's embodied action that mobilizes an accompanying action by a student; (2) allocation of turn-taking and participation while using a digital device; and (3) the affordances of the digital device in relation to the participants' social organization. In this way, it is possible to understand not just what a digital device is or does, but the affordances of what it makes possible in constituting teachers' and students' social and learning relationships.